“I Felt It and I Let It Go”: Perspectives on Meditation and Emotional Regulation among Female Survivors of Interpersonal Trauma with Co-occurring Disorders - Lee, Mo Yee (Journal of family violence, 2022)
Emotional dysregulation poses significant challenges for women who have experienced trauma and can contribute to problems with substance use in an attempt to manage intense emotions and arousal. Various forms of meditation have shown benefits for improved awareness and management of emotions and offer a promising complementary treatment for women in residential substance use treatment who have histories of interpersonal traumas. This qualitative study explored lived experiences with meditation practice and emotional regulation among female trauma survivors with co-occurring substance use and mental disorders. Thirty-two trauma survivors participated in a six-week curriculum at their residential treatment program that included mindfulness, compassion, and loving-kindness meditations. Using an emergent design based on the constant comparative method, the study analyzed qualitative data from individual interviews and focus groups and identified common themes. The findings indicated a perceived pathway through which meditation promoted emotional regulation. This pathway started with increased awareness of their emotions, involved the ability to then accept and let go of their emotions, and ended with emotional growth and improved self-regulation. Though participants portrayed meditation as beneficial, several participants also described suppressed emotions and traumatic memories resurfacing during meditation and described the importance of support from program staff outside of group to help them process and cope. The participants’ perspectives support the appropriateness of meditation as an empowering complementary intervention for female trauma survivors with co-occurring disorders, but also indicate the importance of supervision and support at the start of meditation practice in case negative experiences arise.